Teachers’ Responses to the Demand of Utilizing Online Technology during Pandemic Time - Vidya Putri Cahyani; Henny Soepriyanti (Pusat Riset dan Inovasi Nasional, 2023)
The present study was conducted during school closure during the pandemic period, from 2020 to 2022. This study aims to explore teachers’ responses to the difficulties in using the online platform, and how teachers cope with the challenges in running online classes. This study used a descriptive qualitative approach. Data collection techniques included interviews, observations, and document analysis. The study participants were seven junior high school teachers in Mataram, West Nusa Tenggara. They had mixed work experiences. The results of the study showed that teachers responded differently to the demand for teaching using an online platform. Most teachers conducted online classes on a pro forma basis in order to comply with government policies. They viewed themselves unprepared to participate in online classes. The study also found teachers’ difficulties in teaching online classes due to students’ lack of adequate knowledge, skills and motivation in utilizing the online platforms provided by their schools. The study concludes that there is a need for comprehensive training and support for teachers to effectively adapt to online teaching methods. Additionally, it suggests that schools should invest in improving students' digital literacy skills to enhance their engagement and success in online learning environments.